PEMBUATAN VELVA SAYURAN ( KAJIAN PROPORSI WORTEL, TOMAT, KECAMBAH DAN PENAMBAHAN NA-CMC TERHADAP KUALITAS VELVA SAYURAN ) - Susilowati, Titi; HP, Sudaryati; Candra, Demy Ayu (REKAPANGAN, 2010)
Velva Â is a Â kind Â of Â freezing Â food, Â like Â ice Â cream Â that made Â from Â various Â fruit Â orÂ vegetables. The materials is mixed, homogenized, cooling in the ice cream maker and than wasÂ freezed. Carrot, Â tomato Â and Â mungbean Â sprout are once Â of Â tropical Â vegetables Â can Â be Â used Â asÂ materials for producing velva.Â The research is aimed to know effect of proportion carrot, tomato,mungbean sprout andÂ concentration of Na â CMC Â to quality of velva sayuran.Â The Research used Complete Design Randomized with factorial pattern. The First factorÂ is Â kind Â of Â vegetables Â (carrot, Â tomato, Â and Â mungbean Â sprout); Â the Â  Â second Â factor Â isÂ concentration Â of Â Na â CMC : 0,5%; Â 0,6%; Â 0,7 Â %; Â 0,8%;). Â Ducant Â Multiple Â Range Â Test wasÂ used to know defference of every treatment.Â The Â best Â proportion Â on Â processing Â velva Â vegetables Â is Â 80 Â : Â 80 Â : Â 40(carrot, Â tomato Â andÂ mungbean sprout) and Na- CMC 0,8 %. This treatment is giving the highest overrun is 20,495Â %; Â smooth Â texture Â and the Â highest hedonic Â value Â (taste Â and Â aroma). Â The Â result Â of Â chemical Â analysis showed Â that Aw 68,95 %, Caroten total 59,89 %, Vitamin C 68,39%, Vitamin E 24,33Â % and Total Soluble Solid 32,47 %.Key Word : Velva Vegetables, Carrot, Tomato, Mungbean Sprout And Na - CMC